Islam and Prosper Indonesia: Contestation and Fragmentation of Contemporary Islamic Thought - Yusdani (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
The following article examines Islamic thought and changes in state structure in Indonesia since the reform era from 1998 to the present. The fundamental change of state order in Indonesia is marked by the amendment of the 1945 Constitution and the wide space open for the people to participate in the life of the country. In this situation, progressive Islam, mainstream Islam, and political Islamist thought emerged. The main problem in this article is how Islamic thought is transformed by three variants of Indonesian Muslims in changing state order in the reformation era of Indonesia. The basic theoretical framework that is used to explain Islamic thought and changes of state order above, in addition to using the people's approach as full citizens before the state, also uses a socio-historical approach, political economy. Then the analysis used in this article is political philosophy. The main sources used are the official publications and decisions of each figure and organization related to changes in state order during the reformation era in Indonesia from 1998 to the present. The results of the study can be concluded that three variants of Islamic thought in Indonesia that are very prominent in responding to and directing the changes in state order in Indonesia become a just and welfare state.